Sperm fluorescent in situ hybridisation study of interchromosomal effect in six Tunisian carriers of reciprocal and Robertsonian translocations. (15th January 2018) - Hajlaoui, A.; Slimani, W.; Kammoun, M.; Sallem, A.; Braham, S.; Bibi, M.; Saad, A.; Mougou‐Zerelli, S.
Summary: Carriers of structural chromosomal anomalies, translocations and inversions are at increased risk of aneuploid gametes production. Besides the direct effect on the involved chromosomes, these rearrangements might disturb the segregation of other structurally normal chromosomes during meiosis. Such event is known as interchromosomal effect. In this study, six male carriers of translocations, four reciprocals and two Robertsonians, were investigated. In addition, seven fertile men with normal 46, XY karyotypes and normal sperm characteristics were enrolled as a control group. Spermatic fluorescent in situ hybridisation specific for chromosomes X, Y, 18, 21 and 22 was carried out. The Mann–Whitney U ‐test was used to compare the aneuploidy rates between patients and controls. All translocation carriers showed significantly increased frequencies of disomy of all investigated chromosomes, and diploid gametes compared with the control group ( p  <   .05). However, disomy XY was not significantly different between controls and patients ( p  >   .05). We have also observed a considerable interindividual variability in disomy and diploidy rates. These results confirm that the interchromosomal effect seems to exist and could contribute to higher rates of abnormal prenatal aneuploidy, resulting in a small increase in the risk of miscarriage and birth of children with congenital abnormalities and a potential reduction in fertility.